2009
DOI: 10.1017/s0031182008005453
|View full text |Cite
|
Sign up to set email alerts
|

A novel phylogeny for the genus Echinococcus, based on nuclear data, challenges relationships based on mitochondrial evidence

Abstract: The taxonomic status of Echinococcus, an important zoonotic cestode genus, has remained controversial, despite numerous attempts to revise it. Although mitochondrial DNA (mtDNA) has been the source of markers of choice for reconstructing the phylogeny of the genus, results derived from mtDNA have led to significant inconsistencies with earlier species classifications based on phenotypic analysis. Here, we used nuclear DNA markers to test the phylogenic relationships of members of the genus Echinococcus. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 56 publications
14
121
2
2
Order By: Relevance
“…shiquicus, the nuclear DNA phylogenies of Knapp et al (2011) are in agreement with the mtDNA phylogenies of Nakao et al (2007Nakao et al ( , 2013b and Hüttner et al (2008), while the phylogeny of Saarma et al (2009) suggests a different topology. With respect to E. canadensis, all phylogenies indicate a monophyletic origin, except for that based on exon sequences of nuclear DNA genes by Knapp et al (2011), which suggests that the G6 genotype is more closely related to E. ortleppi than to the other genotypes of E. canadensis.…”
Section: Phylogenetic Patternsupporting
confidence: 61%
See 2 more Smart Citations
“…shiquicus, the nuclear DNA phylogenies of Knapp et al (2011) are in agreement with the mtDNA phylogenies of Nakao et al (2007Nakao et al ( , 2013b and Hüttner et al (2008), while the phylogeny of Saarma et al (2009) suggests a different topology. With respect to E. canadensis, all phylogenies indicate a monophyletic origin, except for that based on exon sequences of nuclear DNA genes by Knapp et al (2011), which suggests that the G6 genotype is more closely related to E. ortleppi than to the other genotypes of E. canadensis.…”
Section: Phylogenetic Patternsupporting
confidence: 61%
“…While phylogenies from mtDNA and some nuclear gene sequences show E. ortleppi as a sister group to the genotypes of E. canadensis (Nakao et al, 2007(Nakao et al, , 2013bSaarma et al, 2009), other nuclear phylogenies are unable to resolve the relationship (Knapp et al, 2011). If the genotypes of E. canadensis are not monophyletic, they clearly cannot be regarded as a single evolutionary species, but if we accept the mtDNA phylogeny as a true reconstruction of evolutionary history, then they may be.…”
Section: Echinococcus Canadenismentioning
confidence: 99%
See 1 more Smart Citation
“…These informal groupings were retained for many years but with the advent of molecular characterization they were shown to be genetically distinct (Thompson and McManus, 2001). PCR-based techniques using a variety of genetic loci, and sequencing of nuclear and mitochondrial DNA, coupled with molecular epidemiological studies in endemic areas, confirmed the genetic and morphological distinctness of the host-adapted strains and revealed phylogenetic relationships which support a robust, meaningful taxonomy based on a previously documented nomenclature (Table 2; Bowles et al, 1994;Cruz-Reyes et al, 2007;Harandi et al, 2002;Huttner et al, 2009;Jenkins et al, 2005Lavikainen et al, 2003Moks et al, 2008;Nakao et al, 2013;Pednekar et al, 2009;Romig et al, 2006Romig et al, , 2015Saarma et al, 2009;Thompson et al, 1995Thompson et al, , 2006Thompson, 2001Thompson, , 2008Thompson and McManus, 2002;Tigre et al, 2016). Interestingly, the nomenclature used for these 'species' conforms to that proposed by observational parasitologists in the 1920se60s, before molecular tools were available to confirm and support their morphological descriptions and epidemiological observations Thompson and McManus, 2002;Thompson, 2008).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 62%
“…granulosus is characterized by high genetic diversity; ten variants/genotypes (G1-G10) have been reported (Eckert and Thompson 1997). The taxonomy of the genus Echinococcus has been recently revised based on the complete mitochondrial genome (Nakao et al, 2007) and on nuclear data (Saarma et al, 2009). Thus today, E. granulosus is considered as complex consisting of four species: E. granulosus sensu stricto (s.s.) (G1-G3), E. equinus (G4), E. ortleppi (G5), and E. canadensis (G6- The phylogenetic relations within E. canadensis (G6-G10) remain under controversial discussion.…”
Section: Introductionmentioning
confidence: 99%